Therapeutic Targeting of Nonalcoholic Fatty Liver Disease by Downregulating SREBP-1C Expression via AMPK-KLF10 Axis - Chen, Yu-Chi; Chen, Rong-Jane; Peng, Szu-Yuan; Yu, Winston C. Y.; Chang, Vincent Hung-Shu (Frontiers in Molecular Biosciences, 2021)
Krüppel-like factor 10 (KLF10) is a phospho-regulated transcriptional factor involved in many biological processes including lipogenesis; however, the transcriptional regulation on lipogenesis by KLF10 remains largely unclear. Lipogenesis is important in the development of nonalcoholic fatty liver disease (NAFLD) which was known regulated mainly by AMP-activated protein kinase (AMPK) and sterol regulatory element-binding protein (SREBP-1C). Interesting, our previous study using phosphorylated site prediction suggested a regulation of AMPK on KLF10. Therefore, we aimed to study the protein–protein interactions of AMPK on the regulation of KLF10, and to delineate the mechanisms of phosphorylated KLF10 in the regulation of NAFLD through SREBP-1C. We performed in vitro and in vivo assays that identified AMPK phosphorylates KLF10 at Thr189 and subsequently modulates the steady state level of KLF10. Meanwhile, a chromatin immunoprecipitation–chip assay revealed the novel target genes and signaling cascades of corresponding to phosphorylated KLF10. SREBP-1C was identified as a target gene suppressed by phosphorylated KLF10 through promoter binding. We further performed high-fat-diet-induced NAFLD models using hepatic-specific KLF10 knockout mice and wild-type mice and revealed that KLF10 knockout markedly led to more severe NAFLD than that in wild-type mice. Taken together, our findings revealed for the first time that AMPK activates and stabilizes the KLF10 protein via phosphorylation at Thr189, thereby repressing the expression of SREBP-1C and subsequent lipogenesis pathways along with metabolic disorders. We suggested that the targeted manipulation of liver metabolism, particularly through increased KLF10 expression, is a potential alternative solution for treating NAFLD.